THE ROLE OF BRAND PERSONALITY APPEAL AND SELF-BRAND CONNECTION IN DETERMINING BRAND RESONANCE - Nurafni Rubiyanti; Zurina Mohaidin (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
This study intends to explore factors influencing brand resonance of cosmetic product in Indonesia. This research used an on-line cross-sectional survey to obtain data concerning the purchase of respondents’ cosmetic favourite brands. The target population for this paper encompassed women in Bandung city, Indonesia who have favourite cosmetic brands and always use the same brand for more that 6 months (possible existing self-brand connection and brand resonance). The sample was taken in Bandung city collaborating 400 respondents. The data analysis method used is SEM-PLS approach based on the SmartPLS version of 3.2.7. The research scope is seen from the perspective of geography and context. For that matter limited to women in the city of Bandung, Indonesia. Contextually, the research is limited to the cosmetic context and narrowed down to reflect only the views of women in Bandung. The results of the study is brand personality appeal has a positive effect towards brand resonance and self-brand connection mediates the relationship between brand personality appeal and brand resonance.